Prevalence, awareness, treatment and control of hypertension in a self-selected sub-Saharan African urban population: a cross-sectional study. Issue 4 (24th August 2012) - Dzudie, Anastase; Kengne, André Pascal; Muna, Walinjom F T; Ba, Hamadou; Menanga, Alain; Kouam Kouam, Charles; Abah, Joseph; Monkam, Yves; Biholong, Christian; Mintom, Pierre; Kamdem, Félicité; Djomou, Armel; et al.
Abstract : Objectives: Hypertension has been established as a major public health problem in Africa, but its specific contributions to disease burden are still incompletely understood. We report the prevalence and determinants of hypertension, detection, treatment and control rates among adults in major cities in Cameroon. Design: Cross-sectional study. Settings: Community-based multicentre study in major cities in Cameroon. Participants: Participants were self-selected urban dwellers from the Center, Littoral, North-West and West Regions, who attended on 17 May 2011 a screening campaign advertised through mass media. Primary and secondary outcomes measures: Hypertension defined as systolic (and/or diastolic) blood pressure (BP)≥ 140 (90) mm Hg, or ongoing BP-lowering medications. Results: In all, 2120 participants (1003 women) were included. Among them, 1007 (prevalence rate 47.5%) had hypertension, including 319 (awareness rate 31.7%) who were aware of their status. The prevalence of hypertension increased with age overall and by sex and region. Among aware hypertensive participants, 191 (treatment rate 59.9%) were on regular BP-lowering medication, and among those treated, 47 (controlled rate 24.6%) were at target BP levels (ie, systolic (and diastolic) BP<140 (90) mm Hg). In multivariable logistic regression analysis, male gender, advanced age, parental history of hypertension, diabetes mellitus, elevated waist and elevated body mass index (BMI) were the significant predictors of hypertension. Likewise, male gender, high BMI and physical inactivity were associated with poor control. Conclusions: High prevalence of hypertension with low awareness, treatment and control were found in this urban population; these findings are significant and alarming with consideration to the various improvements in the access to healthcare and the continuing efforts to educate communities over the last few decades.